Threshold Concepts and Design for Social Change - Souleles, Nicos; Ferreira, Ana Margarida; Savva, Stefania (My University, 2020)
The transition from ambiguous and unclear areas of academic enquiry towards well-defined knowledge boundaries confronts design for social change. Research relevant to the epistemological dimensions of the related academic discipline is limited. Identification of Threshold Concepts (TCs) unique to this academic area can help define appropriate knowledge boundaries. TCs are essential knowledge portals that, once mastered, can result in a transformed way of developing knowledge. Transformation may be emergent or protracted. This paper identifies a number of TCs and elaborates on their significance. Data were collected through a questionnaire with participants from academic and social design practice. This paper argues that it is of educational value to consider that some TCs in the related Higher Education (HE) curricula have to do with ways of thinking and practice, rather than the mastering of discrete conceptual ideas. This has implications for curriculum development in the area of design for social change.
Keywords: Design for social change; Higher education curricula; Social design; Threshold Concepts